Asymmetric Hybridity: Glocalization, Deterritorialized Islam, and Malay Muslim Identity in Pekanbaru - Imron Rosidi; Mhd Ismail bin Sulaiman; Irhason (Balai Penelitian dan Pengembangan Agama Jakarta, 2026)
The Riau Malay people, who are identified as Muslims, have not been immune to the wave of contemporary globalisation that is shaping their way of life. This article examines the construction of Muslim Malay identity in Pekanbaru, exploring how transnational flows of Islamic knowledge interact with local Malay traditions and Indonesian national culture. This qualitative study is based on interviews and observation, analysed through the lenses of glocalisation (Robertson), global cultural flows (Appadurai) and the deterritorialisation of Islam (Roy), alongside literature on the ‘conservative turn’ in Indonesian Islam. The findings reveal a paradox: globalisation gives rise to a hybrid identity comprising local Malay, national Indonesian and transnational Islamic elements, whilst simultaneously intensifying Islamic identity as social media da’wah and religious activities in public spaces expand. This hybridity is asymmetrical—the religious layer is on the rise and becoming increasingly deterritorialised, whilst Malay elements persist as residual markers rather than organising centres—indicating a deterritorialised re-Islamisation: Islam is detached from local customs and re-anchored within a standardised transnational register.